2009 18th International Conference on Parallel Architectures and Compilation Techniques 2009
DOI: 10.1109/pact.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Core-Selectability in Chip Multiprocessors

Abstract: The centralized structures necessary for the extraction of instruction-level parallelism (ILP) are consuming progressively smaller portions of the total die area of chip multiprocessors (CMP). The reason for this is that scaling these structures does not enhance general performance as much as scaling the cache and interconnect. However, the fact that these structures now consume less proportional die area opens an avenue to enhancing their performance through truly overcoming the one-size-fits-all approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Cache sharing solutions rely on multiplexing the L1 caches between multiple cores to eliminate much of the state transfer overheads when switching [29,32]. Other researchers have proposed multiplexing pipeline stages between cores to achieve heterogeneity [30].…”
Section: Fine-grained Approachesmentioning
confidence: 99%
“…Cache sharing solutions rely on multiplexing the L1 caches between multiple cores to eliminate much of the state transfer overheads when switching [29,32]. Other researchers have proposed multiplexing pipeline stages between cores to achieve heterogeneity [30].…”
Section: Fine-grained Approachesmentioning
confidence: 99%
“…We also assume that the serial core is gated off in parallel mode to save power for throughput-oriented dim cores. We study both conventional out-of-order core, such as Core i7, as well as core-selectability [12]. We find that even with an embarrassingly parallel application, the die area investment on a dedicated O3 core is still beneficial.…”
Section: Alternative Serial Coresmentioning
confidence: 99%
“…In [32], Gibson et al propose a forward flow architecture where the execution logic can be scaled to meet the requirements of the incoming workloads. In [9], Najaf-abadi et al propose core selectability where each "node" in the system consists of different types of cores that share common resources. Depending on the application, the respective core from the node is selected to serve that application.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have shown that symmetric cores are unlikely to provide better performance than a heterogeneous multicore [13], [18]. Further studies [9], [16], [18], [33], [36] have shown that reconfigurable architectures may increase the benefits of AMPs even further. This provides a strong argument for our target multicore architecture.…”
Section: Introductionmentioning
confidence: 99%